1967
DOI: 10.1139/v67-043
|View full text |Cite
|
Sign up to set email alerts
|

Étude quantitative des réactions d'ozonolyse. IV. Ozonation de l'indène

Abstract: R e~u le 30 mai 1966The ozonolysis of indene in ethanol yields 3-hydroxy-4,5-benzo-7-ethoxy-l,2-dioxacycloheptane and 3-ethoxy-4,5-benzo-7-hydroxy-l,2-dioxacycloheptane, roughly in a 1:l ratio, thus showing that the cleavage of the primary indene ozonide follows the two possible courses: For personal use only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 5 publications
2
12
0
Order By: Relevance
“…Ozonolyses of a number of unsaturated cyclic compounds in methanol have been reported to give cyclic hemiperacetals (1)(2)(3)(4). In line with this, we found that ozonolysis of l-methylcyclopentene in methanol gave l a , 8a, and l l a in a molar ratio of 90:8:2 (5).…”
Section: Introductionsupporting
confidence: 87%
“…Ozonolyses of a number of unsaturated cyclic compounds in methanol have been reported to give cyclic hemiperacetals (1)(2)(3)(4). In line with this, we found that ozonolysis of l-methylcyclopentene in methanol gave l a , 8a, and l l a in a molar ratio of 90:8:2 (5).…”
Section: Introductionsupporting
confidence: 87%
“…It was reported that the largest negative charge in the ground state is located on the oxygen atom of the carbonyl group present in the coniferyl aldehyde molecule. [33] When the particles coated with coniferyl aldehyde are illuminated by simulated sunlight, the negative charge on the oxygen atom of the C=O group further increases when the molecule is excited from the ground state to the triplet state. The latter implies a raise of the nucleophilic properties of the molecule which is most likely responsible for the high reactivity of carbonyl compounds in their excited triplet states.…”
Section: First-order Rate Constantsmentioning
confidence: 99%
“…[51][52] Fliszar et al exhibited that in cases where an organic compound contains both an aromatic ring and a C=C alkene bond the ozone attacks preferentially the C=C bond. [33] Coniferyl aldehyde contains both an aromatic ring and an unsaturated alkene C=C bond. Therefore, we suggest that the reaction of gas-phase ozone with coniferyl aldehyde proceeds via a concerted cycloaddition process which implies a bridging addition of ozone to the C=C bond as depicted in Scheme 1.…”
Section: Ozonolysis Mechanismmentioning
confidence: 99%
See 2 more Smart Citations